Morphology and composition of the internal axis in two morphologically contrasting deep-water sea pens (Cnidaria: Octocorallia). Issue 11 (27th March 2018) - de Moura Neves, Bárbara; Edinger, Evan; Wareham Hayes, Vonda
ABSTRACT: Umbellula encrinus Linnaeus, 1758 and Anthoptilum grandiflorum (Verrill, 1879) are two species of deep-water sea pens (Cnidaria: Octocorallia) commonly found in the Northwest Atlantic. These sea pens are frequently caught as fishing bycatch, but little is known about their biology. Here we characterise the internal skeleton (axis) of these two morphologically contrasting species, in terms of axis carbonate composition and proportion, morphology and metrics (i.e. cross-sectional area and weight) through gradients along their lengths. Using the conspicuous growth rings present in the axis of U. encrinus we also estimated intra-colonial variation in radial growth rates for this species. X-ray diffraction (XRD) analyses revealed that the carbonate portion of the axis is composed of magnesian calcite (Ca, Mg)CO3 in both species. On average, the axis is composed of 71% carbonate material in U. encrinus, and 65% carbonate in A. grandiflorum . The carbonate proportion was greatly reduced from base (71%) to tip (33%) in the axis of U. encrinus, while in A. grandiflorum changes were less abrupt (~6% difference from base to tip). In U. encrinus, the axis is quadrangular in shape through its whole length, twisting longitudinally. Twisting can occur in both clockwise and anti-clockwise directions. The axis of A. grandiflorum varied from elliptical near the base to cylindrical through most of the remaining length, with no twisting observed. Axes' cross-sectional areas also decreased with distance from the base in both species, being the largest near the base. Estimated radial growth rates in U. encrinus were variable within a single colony, ranging between 0.04 and 0.08 mm.yr −1 . This is the first study to describe changes along the axes of sea pens, and to characterise the axes in the studied species. It provides a baseline for studies considering sea pens' skeletons (e.g. ocean acidification and palaeoceanography).